ON THE NATURE OF ASYMMETRY OF THE LIGHT CURVES OF BM Cas - A LONG PERIOD ECLIPSING SUPERGIANT BINARY - Kalv, P.; Harvig, V.; Aas, T.; Pustylnik, I. (Одеські астрономічні публікації, 2017)
We report results of the analysis of UBVR light curves of the long period eclipsing binary BM Cas obtained between 1967 and 1996 in Tallinn observatory. The asymmetry of the light curves and color variations are discussed and interpreted in terms of a hot extended region close to the neck connecting the critical Roche lobes of the components.